Exploring Protective Factors in Wellbeing: How Sensory Processing Sensitivity and Attention Awareness Interact With Resilience - Gulla, Bożena; Golonka, Krystyna (Frontiers in Psychology, 2021)
The aim of the study is to analyze the relationship between sensory processing sensitivity, attention awareness and resilience and to determine whether attention awareness may moderate the relation between sensitivity and resilience. The sample consisted of 273 adults (239 women; Mage=24.12, SD=6.59 years). The Highly Sensitive Person Scale, the Resilience Measurement Scale, and the Mindful Attention Awareness Scale were used in the study. The results indicate significant relationships between sensory processing sensitivity and resilience; emotional reactivity is especially associated with lower resilience, whereas sensing the subtle is associated with higher resilience. The regression analyses revealed that sensory processing sensitivity is a significant predictor of resilience, but diverse aspects of sensitivity explain resilience differently. Attentional awareness was found to be a significant moderator that strengthens the positive relationship between sensing the subtle and tolerance of negative emotions. The consequences of high sensitivity include high levels of distress, anxiety, and a sense of overload; therefore, searching for protective factors is important to maintain the well-being of highly sensitive people. As one of the characteristics of highly sensitive persons, sensing the subtle may be an important resource that allows to them to deal effectively with difficult situations. Training on attention awareness and conscious presence may be an important way to deal with negative emotions and develop personal competences. The results indicate that these strategies may be of high significance for improving well-being and protecting highly sensitive persons against burnout.